Fixed Point Theorems in Orthogonal Intuitionistic Fuzzy b-metric Spaces with an Application to Fredholm Integral Equation - Fahim Uddin; Muhammad Saeed; Khaleel Ahmad; Umar Ishtiaq; Salvatore Sessa (Transactions on Fuzzy Sets and Systems)
In this manuscript, the concept of an orthogonal intuitionistic fuzzy b-metric space is initiated as a generalization of an intuitionistic fuzzy b-metric space. We presented some fixed point results in this setting. For the validity of the obtained results, some non-trivial examples are given. In the last part, we established an application on the existence of a unique solution of a Fredholm-type integral equation.